Can the STarT Back Tool predict health-related quality of life and work ability after an acute/subacute episode with back or neck pain? A psychometric validation study in primary care. Issue 12 (22nd December 2018) - Forsbrand, Malin H; Grahn, Birgitta; Hill, Jonathan C; Petersson, Ingemar F; Post Sennehed, Charlotte; Stigmar, Kjerstin
Abstract : Objectives: The predictive ability of the STarT Back Tool (SBT) has not yet been examined among acute/subacute back and/or neck pain in a primary care setting in respect to health-related quality of life (HRQoL) and work ability outcomes. The aim of this study was to evaluate the SBT's predictive validity for HRQoL and work ability outcomes at long-term follow-up in a population with acute/subacute back and/or neck pain. Setting: Prospective data from 35 primary care centres in south Sweden during 2013. Participants: Patients (n=329) with acute/subacute back and/or neck pain, aged 18–67 years, not on sick leave or <60 days of sick leave completed the SBT when applying for physiotherapy treatment. Long-term follow-up measures (median 13 months, range 11–27 months) of HRQoL (EQ-5D) and work ability (Work Ability Score) was completed by 238 patients (72%). Outcomes: The predictive ability of the SBT for HRQoL and work ability outcomes was examined using Kruskal-Wallis test, logistic regression and area under the curve (AUC). Results: Based on SBT risk group stratification, 103 (43%), 107 (45%) and 28 (12%) patients were considered as low, medium and at high risk, respectively. There were statistically significant differences in HRQoL (p<0.001) and work ability (p<0.001) at follow-up between all three SBT risk groups. Patients in the high risk group had a significantly increased risk of having poor HRQoL (OR 6.16, 95% CI 1.50 to 25.26) and poor work ability (OR 5.08, 95% CI 1.75 to 14.71) vs the low risk group at follow-up. The AUC was 0.73 (95% CI 0.61 to 0.84) for HRQoL and 0.68 (95% CI 0.61 to 0.76) for work ability. Conclusions: The SBT is an appropriate tool for identifying patients with a poor long-term HRQoL and/or work ability outcome in a population with acute/subacute back and/or neck pain, and maybe a useful adjunct to primary care physiotherapy assessment and practice. Trial registration number: NCT02609750 ; Results.